Injections of hope: supporting participants in clinical trials. (16th December 2021) - Harding, Emma; Robinson, Philip; Wilson, James; Crutch, Sebastian J; Mummery, Catherine J
Abstract : Understanding hope and better appreciating the personal investments of trial participants could improve patient experience and trial design, argue Emma Harding, Catherine Mummery, and colleagues